2019
DOI: 10.1159/000502839
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience of Superb Microvascular Imaging for Key Cardiac Views in Foetal Assessment before 15 Weeks Gestation

Abstract: Background: In the first trimester, ultrasound confirmation of normal or abnormal cardiac anatomy is difficult. B-mode and colour flow Doppler (CFD) are used to assess the foetal heart. Superb microvascular imaging (SMI) can visualise blood flow within the heart and vessels in early gestation. Objective: We report an initial experience of SMI for visualisation of normal and abnormal cardiac anatomy in the first trimester. Methods: Transabdominal foetal echocardiography was performed between 11 + 6 and 14 + 3 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Jabak et al reported that intracardiac structures could be more clearly visualized by SMI at less than 15 weeks of gestation compared with conventional color Doppler and B-mode methods, resulting in "virtual" contrast imaging. 16 In our case, the irregular contours on the endocardial surface of the anatomical left ventricle, indicating prominent trabeculations of the left ventricle, were visible from 15 weeks of gestation onward. In the SMI image of normal cardiac structure at the same week of gestation, the left ventricular endocardial surface was smooth (Figure 2c).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Jabak et al reported that intracardiac structures could be more clearly visualized by SMI at less than 15 weeks of gestation compared with conventional color Doppler and B-mode methods, resulting in "virtual" contrast imaging. 16 In our case, the irregular contours on the endocardial surface of the anatomical left ventricle, indicating prominent trabeculations of the left ventricle, were visible from 15 weeks of gestation onward. In the SMI image of normal cardiac structure at the same week of gestation, the left ventricular endocardial surface was smooth (Figure 2c).…”
Section: Discussionsupporting
confidence: 48%
“…This enables the description of blood flow mapping at high resolutions, which cannot be depicted using conventional Doppler modes. Jabak et al reported that intracardiac structures could be more clearly visualized by SMI at less than 15 weeks of gestation compared with conventional color Doppler and B‐mode methods, resulting in “virtual” contrast imaging 16 . In our case, the irregular contours on the endocardial surface of the anatomical left ventricle, indicating prominent trabeculations of the left ventricle, were visible from 15 weeks of gestation onward.…”
Section: Discussionmentioning
confidence: 51%
“…This could potentially identify vulnerable plaques and have important implications in stroke management 17 . Additional vascular studies of SMI focused on endo‐leaks after aortic grafting, visualization of hepatic artery after liver transplant, cardiac imaging in fetuses, and assessment of intracranial vasculature in neonatal transcranial ultrasonography 18‐21 . A single case report also demonstrated possible utility of SMI in characterization of wall inflammation in Takayasu arteritis 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar advanced flow-detection imaging techniques are also currently marketed under various trademarks (Hasegawa et al 2019;Mack et al 2019;Hata et al 2020aHata et al , 2020bJabak et al 2020;Sainz et al 2020). These applications include Superb Microvascular Imaging (SMI) by Canon Medical Systems (formerly Toshiba Medical Imaging), Detective Flow Imaging (DFI) by Hitachi Medical Systems, microflow imaging (MFI) by Philips and MV-Flow by Samsung Health Care.…”
Section: Introductionmentioning
confidence: 99%